2018
DOI: 10.1038/s41467-018-04379-2
|View full text |Cite
|
Sign up to set email alerts
|

MxB is an interferon-induced restriction factor of human herpesviruses

Abstract: The type I interferon (IFN) system plays an important role in controlling herpesvirus infections, but it is unclear which IFN-mediated effectors interfere with herpesvirus replication. Here we report that human myxovirus resistance protein B (MxB, also designated Mx2) is a potent human herpesvirus restriction factor in the context of IFN. We demonstrate that ectopic MxB expression restricts a range of herpesviruses from the Alphaherpesvirinae and Gammaherpesvirinae, including herpes simplex virus 1 and 2 (HSV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
178
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(185 citation statements)
references
References 78 publications
6
178
1
Order By: Relevance
“…Previous vast research reported that MXA had broad antiviral activities, while MXB was considered lacking antiviral activity. Recent experiments proved MXB protein encoded by MX2 gene was an interferon‐induced restriction factor of HIV‐1 . However, few studies have been done to explore whether the expression level of MX2 gene was related with tumorigenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous vast research reported that MXA had broad antiviral activities, while MXB was considered lacking antiviral activity. Recent experiments proved MXB protein encoded by MX2 gene was an interferon‐induced restriction factor of HIV‐1 . However, few studies have been done to explore whether the expression level of MX2 gene was related with tumorigenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…31 protein encoded by MX2 gene was an interferon-induced restriction factor of HIV-1. [19][20][21] However, few studies have been done to explore whether the expression level of MX2 gene was related with tumorigenesis and progression. Our work found that relative messenger RNA (mRNA) levels of MX2 were significantly reduced in both GBM tissues and four glioma cells compared to normal tissues and cells, especially in U251 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To directly visualize HSV-1 entry in macrophages and fibroblasts, we performed electron microscopy of macrophages and fibroblasts, which were infected with HSV-1 (MOI 250) for 30 min. We chose 30 min, as this is the time that HSV-1 requires to enter cells and first incoming capsids to reach the nuclear envelope of fibroblasts or epithelial cells 11,[32][33][34] . Indeed, 30 min after infection we detected first viral capsids at the nuclear envelope of fibroblasts, but no newly produced viral capsids ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1A). We used wild type AdV-C2 and immuno-staining, or the GFP-expressing replication-competent AdV-C2-dE3B-GFP, AdV-C2-dE3B-dADP, AdV-C2-V-GFP, HSV-1-VP16-GFP, HSV-1 C12 viruses (44)(45)(46). For AdV, we acquired images at 72 h post infection (pi), and for HSV-1 at 48 h pi, reflecting the different replication times of the viruses.…”
Section: Machine-labelling Identifies Hsv-1 and Adv-infected Cells Inmentioning
confidence: 99%